The Role of Melatonin in Modulating Morphometric Parameters and Bioactive Compounds of Brassica oleracea L. var. italica Plenck Under Drought Stress - Donata Arena; Hajer Ben Ammar; Victor Manuel Rodriguez; Pablo Velasco; Riccardo Calì; Luca Ciccarello; Ferdinando Branca (Agronomy)
Drought stress significantly affects plant growth, productivity, and yield by inducing morphological, physiological, and biochemical changes. This study evaluates exogenous melatonin effects on agronomic and biochemical traits of two broccoli varieties (Brassica oleracea L. var. italica Plenck) at the baby-leaves stage under drought stress. The varieties used were the Sicilian sprouting black broccoli, Broccolo nero (BR), and the commercial one, Cavolo Broccolo Ramoso Calabrese (CR). The experiment was conducted in a cold greenhouse in Catania, Sicily, considering two levels of melatonin (0 and 100 µmol L−1) under two irrigation regimes: 100% and 60% of pot water capacity (I100 and I60). Plant weight, SPAD index, and leaf parameters were affected by the melatonin treatment, irrigation regime, and genotypes. Total glucosinolates were highest in BR under melatonin treatment (M1) at full irrigation (I100). Significant differences were observed for glucosinolates and phenolic profiles. Specifically, CR showed significantly higher glucoraphanin content compared to BR. CR, in response to the combined M1-I60 treatment, exhibited a marked increase in total phenolic content (TPC), reaching its highest level among the tested conditions. Similarly, antioxidant capacity, evaluated through ABTS and FRAP assays, showed a significant improvement in BR under combined treatments. Additionally, the caffeic acid hexose varies from 5.11 to 8.93% for control (M0) and melatonin application (M1). These findings highlight melatonin’s potential to mitigate drought stress effects in broccoli.